Alcohol consumption, cigarette smoking and incidence of aortic valve stenosis. (1st June 2017) - Larsson, S. C.; Wolk, A.; Bäck, M.
Abstract: Background: Alcohol consumption and cigarette smoking are modifiable lifestyle factors with important impact on public health. It is unclear whether these factors influence the risk of aortic valve stenosis (AVS). Objective: To investigate the associations of alcohol consumption and smoking, including smoking intensity and time since cessation, with AVS incidence in two prospective cohorts. Methods: This analysis was based on data from the Swedish Mammography Cohort and the Cohort of Swedish Men, comprising 69 365 adults without cardiovascular disease at baseline. Participants were followed for AVS incidence and death by linkage to the Swedish National Patient and Causes of Death Registers. Hazard ratios (HR) with 95% confidence intervals (CI) were estimated by Cox proportional hazards regression. Results: Over a mean follow‐up of 15.3 years, 1249 cases of AVS (494 in women and 755 in men) were recorded. Compared with never drinkers of alcohol (lifelong abstainers), the risk of AVS was significantly lower in current light drinkers (1–6 drinks per week [1 drink = 12 g alcohol]; multivariable HR 0.82; 95% CI: 0.68–0.99). The risk of AVS increased with increasing smoking intensity. Compared with never smokers, the HR was 1.46 (95% CI: 1.16–1.85) in current smokers of ≥30 pack‐years. Former smokers who had quit smoking 10 or more years previously had similar risk for AVS as never smokers. Conclusions: This study suggests that current light alcohol consumption is associated with a lower risk of AVS, and indicates that the association between smoking and AVS risk is reversible.